ANALISIS PEMANFAATAN LABORATORIUM DAN PELAKSANAAN PRAKTIKUM PADA PEMBELAJARAN BIOLOGI DI LABORATORIUM SMA - Dwi Rini Kurnia Fitri; Liza Wahyu (Bioilmi: Jurnal Pendidikan, 2023)
Utilization of laboratories and implementation of Biology practicum in schools shows the fact that they have not been carried out optimally, this is due to the many obstacles and many problems for carrying out activities in the laboratory. Limitations and infrequent implementation of practicum and lack of availability of laboratory supporting facilities and infrastructure. This study aims to describe the use of the laboratory and the implementation of practicum in Biology learning in the laboratory of SMA Negeri 1 Padang Ganting. This research is a qualitative descriptive study. Data collection techniques were carried out using triangulation techniques, namely observation, interviews and documentation which included data on laboratory utilization and practicum implementation. The results showed that the average percentage of laboratory utilization and practicum implementation was 79.25% and 82.02%, respectively, in the good and very good categories. This indicates that the utilization of the laboratory and the implementation of practicum at SMA Negeri 1 Padang Ganting is good.